Lower dynamic neck strength is associated with history of concussion in varsity female soccer players - Versteegh, T. (British Journal of Sports Medicine, 2021)
Background There is mounting evidence that dynamic neck strength may play a role in protecting against concussion. It is also well established that athletes with a prior history of concussion are at higher risk than those with no prior history.